2023
DOI: 10.1155/2023/5685174
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Optimization, Preliminary Identification, and Bioactivities in Corn Silk

Abstract: For thousands of years, corn silk has been widely used as an antidiabetic, antioxidant, and antihyperlipidemic and for other effects, but there is a lack of studies that correlate the extracts of flavonoid composition with their biological activities. Thus, the objectives of this study were to optimize the conditions for extracting flavonoids, identify flavonoids, and correlate the flavonoid composition with the biological activities in corn silk. The response surface experiments showed that the highest flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…There have been some previous studies regarding different optimization of extraction techniques applied to CS, aiming to optimize the extraction yield of flavonoids [44], polysaccharides using simple extraction [45], or pulsed electric field extraction [46]. Furthermore, we have chosen to develop a mathematical model using two dependent variables, specifically TFC and ABTS, aiming to maximize (a) the total yield of flavonoid species and (b) the total antioxidant activity of the phytocompounds that are successfully extracted.…”
Section: Optimization Of Extractionmentioning
confidence: 99%
“…There have been some previous studies regarding different optimization of extraction techniques applied to CS, aiming to optimize the extraction yield of flavonoids [44], polysaccharides using simple extraction [45], or pulsed electric field extraction [46]. Furthermore, we have chosen to develop a mathematical model using two dependent variables, specifically TFC and ABTS, aiming to maximize (a) the total yield of flavonoid species and (b) the total antioxidant activity of the phytocompounds that are successfully extracted.…”
Section: Optimization Of Extractionmentioning
confidence: 99%
“…Furthermore, western blotting results indicated that the extract primarily decreased serum UA by influencing GLUT9, OAT1 and URAT1, and by inhibiting XOD activity in mice (48). Corn silk, the style and stigma of the gramineous plant Zea mays L., also known as Yu Shu Li Rui, is both a traditional food and medicine in China, with flavonoids being its most effective components (49). These flavonoids, found in high concentrations in all parts of the corn plant (50), can reduce UA levels in hyperuricemia, effectively treating gout and gouty arthritis (51).…”
Section: Ua Transporter and Gouty Arthritismentioning
confidence: 99%
“…Corn silk contains important phenolic compounds that may fight dementia. The bioactive compounds of corn silk have demonstrated antioxidant, antimutagenic, antiproliferative, anti-inflammatory, antihyperglycemic, antidiabetic, antibacterial, antifungal, antihyperlipidemic, antidepressant, antihypertensive, antihyperlipidemic, antiadipogenic, and anti-fatigue activities [1,6]. In addition, research Trends Sci.…”
Section: Introductionmentioning
confidence: 99%